Optic Nerve Demyelination Along with Cardiorespiratory Involvement: A Rare Presentation of Multisystem Inflammatory Syndrome in Children - Jayant Kumar Muduli; Meenakshi Mitra; Shivam Mahipal (Wolters Kluwer Medknow Publications, 2023)
Background: Multisystem inflammatory syndrome in children (MIS-C) has been described as an illness consisting of inflammation of more than one system of the body with raised inflammatory biomarkers following an infection of COVID-19. There is growing literature regarding the clinical spectrum of the condition. We report an unusual presentation of optic nerve demyelination in a child diagnosed with MIS-C. Clinical Description: A 3 years, 10-month-old boy presented with fever, generalized maculopapular rash, conjunctivitis, and bilateral palmar erythema. On examination, the child was febrile with tachypnea, tachycardia, and engorged jugular veins. Chest auscultation revealed basal crepitation. The cardiovascular examination was unremarkable. He had tender hepatomegaly. He developed photophobia and poor vision on the fourth day of admission with weakness of limbs. Ophthalmological examination showed a loss of visual acuity (perception of light only), while the fundoscopy examination was normal. Management: Inflammatory biomarkers and COVID-19 antibody titers were elevated. Echocardiography (ECHO) showed dilatation of the coronary arteries and poor ejection fraction. Magnetic resonance imaging of the brain showed bilateral optic nerve demyelination. Thus, the diagnosis was consistent with MIS-C with optic neuritis. Treatment was initiated with intravenous immunoglobulin (IVIG) and intravenous methylprednisolone with other supportive measures. At the 3-week follow-up, the child's vision, power in all four limbs, and echo parameters improved. Conclusion: This case creates awareness regarding optic neuritis as a rare presentation of MIS-C with cardiorespiratory and neurological involvement, successfully managed with IVIG and steroids.